Teaching the Short Story
XVII, 204 p.
Keywords: The short story is moving from relative neglect to a central position in the curriculum; as a teaching tool, it offers students a route into many complex areas, including critical theory, gender studies, postcolonialism and genre. This book offers a practical guide to the short story in the classroom, covering all these fields and more.